Oligogaster gen. nov., a new chrysidid genus from Egypt (Hymenoptera, Chrysididae, Elampini) - Soliman, Ahmed M.; Kimsey, Lynn S. (Zootaxa, 2013)
Oligogaster Soliman & Kimsey, gen. nov. (type species Oligogaster kimseyae Soliman, sp. nov.) from the tribe Elampini is described from Egypt.